2023
DOI: 10.3390/ijms24032125
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNAs as a Diagnostic and Therapeutic Target in Cardiovascular Diseases

Abstract: Circular RNAs (circRNAs) are a family of noncoding RNAs (ncRNAs) that are endogenous and widely distributed in different species, performing several functions, mainly their association with microRNAs (miRNAs) and RNA-binding proteins. CVDs remain the leading cause of death worldwide; therefore, the development of new therapies and strategies, such as gene therapies or nonpharmacological therapies, with low cost, such as physical exercise, to alleviate these diseases is of extreme importance for society. With i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 118 publications
0
4
0
Order By: Relevance
“…The detected circRNAs were considered non-functional or splicing by-products; however, with the development of high-throughput sequencing and bioinformatics approaches, it was found that circRNAs are highly expressed in all eukaryotic cells and perform certain functions [ 35 ]. Recent studies have shown that circRNAs are critical regulators of cell physiology and various pathologies by modulating gene expression [ 29 , 36 , 37 , 38 , 39 ].…”
Section: Characteristics and Functions Of Circrnasmentioning
confidence: 99%
See 2 more Smart Citations
“…The detected circRNAs were considered non-functional or splicing by-products; however, with the development of high-throughput sequencing and bioinformatics approaches, it was found that circRNAs are highly expressed in all eukaryotic cells and perform certain functions [ 35 ]. Recent studies have shown that circRNAs are critical regulators of cell physiology and various pathologies by modulating gene expression [ 29 , 36 , 37 , 38 , 39 ].…”
Section: Characteristics and Functions Of Circrnasmentioning
confidence: 99%
“…The use of circRNAs as therapeutic targets in CAD has been widely discussed [ 24 , 29 , 170 ]. An attractive therapy strategy is the creation and use of artificial circRNAs in the form of miRNA sponges [ 171 ].…”
Section: Circrnas Are Promising Biomarkers and Therapeutic Targets Fo...mentioning
confidence: 99%
See 1 more Smart Citation
“… 3 microRNAs are small RNAs that are mainly involved in the regulation of post-transcriptional translation of genes in mammals. 4 Studies have shown that microRNAs can attach to and silence genes involved in the atherogenesis pathway, thereby inhibiting the expression of proteins and cellular functions involved in regulating the stability of atherosclerotic plaques. It is thus possible that microRNAs may represent new targets for research to prevent and treat atherosclerotic diseases.…”
Section: Introductionmentioning
confidence: 99%